The Role Of Teachers In Influenced Religious And Moral Values In Children Multicultural Class For 5-6 Years Old At Satya Prawira Kindergarten Year 2025 - Rindi Yani; M. Arzani; Muhammad Muhajirin (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to describe the role of teachers in instilling religious and moral values, as well as to identify the supporting and inhibiting factors for teachers in multicultural classrooms at Satya Prawira Kindergarten in 2025. This is a descriptive qualitative study. The subjects of this study are 33 students from Group B of Satya Prawira Kindergarten. The focus of the study is the teacher's role in instilling religious and moral values in a multicultural classroom.The results of this study show that teachers play a crucial role in enhancing children's development, especially in terms of religious and moral values. In instilling and developing these values, teachers employ various teaching methods and strategies, such as implementing positive habits, fostering religious tolerance, and creating policies that promote equality among students of different backgrounds.Conclusion: Teachers' efforts in instilling religious and moral values in Group B children can be carried out through cultivating positive habits, fostering tolerance among children, and formulating fair policies that ensure equality among all students from diverse backgrounds.Supporting factors include high levels of tolerance, the habitual development of positive attitudes, a conducive school environment, and adequate facilities and infrastructure.Inhibiting factors include the diversity of cultural and religious backgrounds, differences in values and norms, the challenge of identifying similarities and differences, limited teacher knowledge, and lack of involvement from parents and the community.Keywords:Teacher's role, religious and moral values, multicultural